Didactics of texts and their learning: a cognitive-linguistic approach - abdelkrim, abdelkrim.benmohame (El Omda in Linguistics and Discourse Analysis, 2025)
This study investigates how learners acquire different types of texts in terms of comprehension, storage, and production, from a cognitive linguistics perspective. The use of this knowledge contributes to proposing alternative approaches to teaching and learning texts. One of the main findings of the study is the necessity of relying, in the selection of instructional texts and teaching methods, on the results of contemporary research that has addressed the mental and psychological processes involved in text comprehension, storage, and retrieval, as well as the facilitating factors in this process, particularly in the fields of cognitive linguistics and artificial intelligence.